Linking bacterial diversity to floral identity in the bumble bee pollen basket - Nicholas Sookhan; Antonio Lorenzo; Shinichi Tatsumi; Mandy Yuen; J. Scott MacIvor (Environmental DNA, 2021)
Abstract Multitrophic interactions are ubiquitous in nature and form the basis of biodiversity. For example, bumble bees visit flowers to collect pollen, on which a variety of bacteria exist. Such bacteria consist of pathogens and mutualists and therefore have consequences for bumble bee colony fitness. However, we still know little about how plant diversity and floral selection by bees translate into the bacterial diversity and composition on the pollen consumed by important pollinators. The aim of this study was to characterize the bacterial and floral alpha and beta diversity from bumble bee corbicula (pollen baskets), identify core communities, and characterize their functional role. We found that bacterial alpha diversity (i.e., the diversity of bacteria determined from the pollen basket of a single bumble bee) was positively correlated with floral pollen alpha diversity (i.e., the diversity of plants from that same pollen basket). Bacterial beta diversity (i.e., bacterial composition) was generally weakly correlated with pollen beta diversity (i.e., floral composition). The abundance of some bacterial genera and pollen families was correlated, specifically Lactobacillus and Acinetobacter were positively correlated with Asteraceae pollen and negatively correlated with Lamiaceae pollen. The most widespread bacteria (the “core OTU”) in bumble bee pollen baskets included both possibly beneficial (Lactobacillus) and potentially pathogenic (Pseudomonas) taxa, but more core OTU functions were unknown vs. known for bumble bees, illustrating the importance of understanding bee–flower–microbe relationships in natural settings.